Magnetic and phonon transitions in B-site Co doped BiFeO3 ceramics. Issue 11 (15th August 2016) - Chiang, Yueh-Sheng; Tu, Chi-Shun; Chen, Pin-Yi; Chen, Cheng-Sao; Anthoniappen, J.; Ting, Yi; Chan, Ting-Shan; Schmidt, V.H.
Abstract: Magnetic susceptibility and phonons have been characterized in multiferroic Bi(Fe1− x Co x )O3−δ ceramics for x =0.0, 0.05, and 0.10 (BFO100 x Co) as functions of temperature. A preferred (100) crystallographic orientation and increasing average oxygen vacancies were observed in BFO5Co and BFO10Co. The Fe and Co K-edge synchrotron X-ray absorptions revealed mixed valences of Fe 3+, Fe 4+, Co 2+, and Co 3+ ions in BFO5Co and BFO10Co, which exhibit a ferromagnetic (or ferrimagnetic) phase below room temperature due to appearance of ferromagnetic B–O–B (B=Fe and Co) superexchange interactions. Field–cooled (FC) and zero–field–cooled (ZFC) magnetic susceptibilities exhibit a significant spin-glass splitting below room temperature in BFO5Co and BFO10Co. Two Raman-active phonon anomalies at ~170 K (or 200 K) and ~260 K were attributed to the Fe 3+ –O–Co 3+ and Co 3+ –O–Co 3+ magnetic orderings, respectively. This work suggests that the low-spin Co 2+ –O–Co 2+, Fe 3+ –O–Fe 3+ (or Fe 4+ ), and high-spin Co 2+ –O–Co 2+ superexchange interactions are responsible for phonon anomalies at ~290 (or ~300 K), ~400, and ~470 K (or ~520 K) in BFO5Co and BFO10Co.